Performance of medical schools in Chile facing the new accreditation criteria - Jerez Yañez, Oscar Mauricio; Aguilera Fortes, Ignacio Rodrigo; Campolo, Ignacio Tomás; Aller Acuña, Diego Alejandro; Munita Leiva, Martín; Bravo Osorio, Liseth (Spanish Journal of Medical Education, 2024)
Introduction: Accreditation of medical programs is fundamental to ensure quality in the training of future doctors. Recently, new accreditation criteria have been implemented in Chile in line with international standards. The objective is to evaluate the last accreditation process of medical careers in Chile using the new criteria, with this, identify patterns and lessons learned to improve medical education and align with international standards. Method: The accreditation records of Chilean universities teaching medicine, available on the National Accreditation Commission website, were collected and analyzed. The analysis included a thorough review of the new criteria and a re-evaluation of the accreditations using a three-tiered scale: basic, advanced, and excellence. An analysis of means and variance was performed for each criterion, and careers were grouped by year of accreditation using content and cluster analysis. Results: A high variance was observed among the universities in the evaluated criteria. The criteria with better average performance were graduate profile, curriculum, academic staff, and internal management. The criteria for the worst performance included the results of the educational process, infrastructure, self-regulation, link with the environment, and professional productivity. Clustering revealed three main groups of universities, differentiated by their years of accreditation and compliance with the criteria. Discussion: There are differences in the implementation and fulfillment with the new accreditation criteria and identify areas of strength and weakness. Comparison with the previous process, which spans more than 20 years, allows for the establishment of a baseline for future evaluations and the adjustment of policies to align with international standards. Conclusions: The study provides a detailed overview of the current state of medical education in Chile under the new accreditation criteria and offers recommendations for continuous improvement.